Technology to support aging in place: key messages for policymakers and funders - Genge, Courtney; McNeil, Heather; Debergue, Patricia; Freeman, Shannon (Frontiers in Psychology, 2023)
AgeTech, a subset of the health technology industry, uses technology to support healthy aging, and support care partners and health professionals to improve quality of life for aging adults. By enhancing and adapting alternative care approaches through emerging technologies, it is possible to enable and extend the ability for older adults to safely age in place within their own homes, improve care experiences, and/or decrease long-term care costs/needs. With the rapid development and proliferation of AgeTech into the consumer market, it is paramount for policymakers and funders to ensure that AgeTech solutions can be leveraged to support older adults to age well in place. This paper highlights five key messages for policymakers and funders drawing on experiences from Canada. First, it is essential to embrace a life course perspective on aging, recognizing the heterogeneity of older adults who experience diverse and evolving needs. AgeTech should adapt as needs and capacities evolve. Second, AgeTech should solve a real problem. Technology must be well aligned to the needs and preferences of older adults to be impactful. Third, health related AgeTech should empower, enhance, or support existing health care services, while recognizing the value of human interactions. In-person interactions can provide meaningful connection and important health data which should be enhanced not replaced. Fourth, the establishment and ongoing fostering of authentic partnerships to inform, co-create and co-design AgeTech solutions is key to developing successful products. Finally, policymakers and funders have an important role to play in enabling accelerated design, development and testing to meet current and future needs.Many countries, including Japan, Germany, and Italy are already considered "super-aged" with over 25% of their populations over 65. Many other nations, including the USA, Korea, Sweden, New Zealand, and Australia, are expected to reach this status by 2030 (United Nations, 2022). Similarly, the population of Canada is going through significant demographic shifts, with older adults (65+) becoming the fastest-growing segment and projected to represent 25% of the country's population by 2050 (FP Analytics, 2018). While population aging represents accomplishment and